Ethnopedagogy through Project Based Learning as an Effort to Improve Students’ Self-regulated Learning - Lina Ratna; Andi Ulfa Tenri Pada; Samingan; Hafnati Rahmatan; Safrida (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this research is to determine the impact of applying an ethnopedagogical approach through project based learning (PjBL) on students' self-regulated learning (SRL). This research uses the quasi experimental method and pretest-posttest non-equivalent control group design. As many as 100 of 353 students class X at SMAN 3 Banda Aceh were selected through purposive sampling technique. A non-test instrument was used to measure students' SRL. Data were analyzed using descriptive statistics and an independent sample t test. The result of the hypothesis test illustrates the sig. > 0.05 (0.566 > 0.05), then H0 accepted. The result of descriptive analysis shows that the increase of the average score in the experimental group was greater than the control group after the intervention. Thus, applying an ethnopedagogical approach through PjBL provides a positive impact on increasing the students’ SRL but there is no significant influence.